Abortion: special statistics in the federal districts of Russian Federation - O S Filippov; Z Z Tokova; A S Gata; A A Kuzemin; V V Gudimova (IP Berlin A.V., 2016)
Materials of the prevalence of abortion in the federal districts of Russia.